Study on efficiency calibrating method of well-type γ ray spectrometer for soil samples - LAI Yongfang; CHEN Fei; SUN Jian; QIN Wanyun; QI Yelin (He jishu, 2021)
BackgroundPutting samples into the well-type γ ray spectrometer can greatly improve the activity measurement efficiency, therefore it can reduce the measurement time and the mass of samples.PurposeThis study aims to accurately obtain detection efficiencies of well-type NaI(Tl) detector as a function of gamma ray energy and the well depth before using the well-type γ ray spectrometer.MethodsFirst of all, the Monte Carlo N Particle Transport Code (MCNP) was employed to simulate energy deposition spectrum of γ ray in well-type NaI(Tl) detector according to mathematic model based on the characteristic parameters of detector and standard γ source. Based on simulating a well-type NaI(Tl) detector and soil samples, the peak efficiency of different γ ray energy and depth of soil samples were calculated by MCNP4C program and corrected by single energy point source measurement. Meanwhile the efficiency calibration functions were fitted accoeding to detection efficiency of well type NaI(TI) gamma spectrometer with different energy and quality of soil samples. Finally, 137Cs point source was used for experimental verification for main standard soil samples of SiO2, A12O3, Fe2O3, FeO, MgO and CaO.ResultsThe maximum relative deviation between the function fitting value and the MCNP simulation value is less than ±7%.ConclusionsThe efficiency calibrating method of well-type is established based on the combination of MCNP simulation calculation and volume source measurement correction.